Global sensitivity and uncertainty analysis of the levelised cost of storage (LCOS) for solar-PV-powered cooling. (15th March 2021) - Luerssen, Christoph; Verbois, Hadrien; Gandhi, Oktoviano; Reindl, Thomas; Sekhar, Chandra; Cheong, David
Abstract: In this paper, we investigate the sensitivity of the parameters affecting the levelised cost of storage (LCOS) of Lithium ion (Li-Ion) battery storage and chilled water storage for on-grid PV-powered cooling applications, namely an office and a hotel building. Therefore, we carry out multi-objective optimisations to minimise the LCOS and maximise the self-sufficiency based on TRNSYS simulation models. For selected optimal solutions, we perform Morris and Sobol global sensitivity as well as uncertainty analyses. The results show that the chilled water storage yields up to 8 ctUSD/kWh el lower LCOS than the battery storage at the same self-sufficiency; however, the battery storage can increase the self-sufficiency more. The dominant parameter affecting the LCOS is the storage lifetime for the battery. Careful design of the dedicated chiller plant to charge the storage is important for the system configuration with chilled water storage. Because of the wide range of possible battery lifetimes, the 90% confidence interval for the LCOS of battery storage is 2.6 times larger than the one for chilled water storage given the input parameter ranges in this study. The future trend indicates that battery storage is expected to become more competitive due to technological advancements and favourable price developments. Highlights: Thermal energy storage is less sensitive to influencing parameters. The LCOS for battery storage is more uncertain. Battery storage lifetime is crucial for competitiveness. Optimised thermal energy storage is more cost-effective, but with limitations.